A relevância das línguas originais da bíblia na exegese e os problemas de tradução como principais motivadores para seu uso - Costa Júnior, Belmiro Medeiros da (2013)
Based on translation problems, this paper proposes to demonstrate the relevance of using the original languages in exegesis. This paper is divided into three chapters. In the first chapter we sought to deal with the knowledge of the Hebrew language, presenting its history, characteristics and peculiarities. This first information will lead the reader to perceive the various differences which this language has with regard to the Western languages, thus leading the reader to understand a little of the work demanded to translate the Old Testament. Besides this, there is an explanation about exegesis and how the original languages are important in this process. The pastor or theologian who uses the original languages as instruments in his/her exegetical studies will have a deeper theological content, being less superficial in their sermons. These people will be able to step on surer ground with biblical languages. The second chapter presents a comprehension about translation and its difficulties. It also presents an explanation about the linguistic signals. For one cannot carry out a good translation without having this subject in mind. The linguistic signal will show us that the concepts which we have today about certain words are not the same which the original hearers of the sacred scriptures had more than two thousand years ago in the East. The same chapter intends to present and explain the four types of existing translations. The paper ends with the third chapter, which brings as case studies, nine biblical texts containing some translation problems, such as paronomasia, onomatopoeia, euphemism, meaning ambiguities, possible mistakes in the translation and words which have no satisfactory equivalents in Portuguese. This paper does not intend to show that those who know the original languages and use them will have all the answers in exegesis. The point here is to present to the academic community, exegetes, preachers, among others, some points which give the original languages a great importance in exegesis, inviting them to leave the surface of the sacred text and thus, begin to dig into them 2, since the treasure, which can represent the real intention of the sacred writer, is not always on the surface, but within the text. The reader of this paper will have the perception that Hebrew is a fascinating, instigating and challenging language, because it brings other proposals of meaning and of intention of the text, deconstructing thoughts and even biblical doctrines. Faced with all the responsibility which the theologian, exegete, biblicist and pastor have with regard to the academic, ecclesiastical community and with all of society, to bring answers to the various issues referring to the Sacred Scriptures which arise every moment, there is no denying the importance of this work and its proposal.